2014
DOI: 10.1089/lap.2013.0590
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescence Laparoscopy of the Cystic Duct and Artery in Pigs: Performance of a Preclinical Dye

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. Background: Near-infrared fluorescence laparoscopy after intravenous indocyanine green (ICG) administration has been proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
2
22
1
Order By: Relevance
“…Similar results by Schols et al [10] stated that fluorescence imaging did not prolong surgery length and can be performed at any point during LC.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results by Schols et al [10] stated that fluorescence imaging did not prolong surgery length and can be performed at any point during LC.…”
Section: Discussionsupporting
confidence: 81%
“…The chief drawbacks of laparoscopy compared to open surgery are the lack of three-dimensional visualization and tactile feedback that may result in misinterpretation [7]. In recent years, a technique of using near infrared light and a fluorescent dye to visualize tumors and structures with minimal dissection has gained recognition [8][9][10][11][12]. Literature supported more than 90 % detection of extrahepatic biliary ducts in laparoscopic cholecystectomies (LC) by this imaging method [13].…”
Section: Introductionmentioning
confidence: 99%
“…As such, exploring the feasibility of using a single device, especially those that are already commercially available, to image multiple probes is of current interest to many investigators in the field. Schols et al applied a commercially available NIR laparoscopic imaging device designed for use with indocyanine green to image biliary anatomy using IRDye800CW in pigs (27). We have demonstrated that the limited wavelength overlap was not a deterrent to successful tumor identification or delineation as confirmed by histology.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, false positive lesions have been reported, notably in hepatibiliary surgery field. 137,138 Recently, Schols and colleagues 167 have reported interesting results using a new NIR dye (CW800-CA) showing the same characteristics as ICG. They found that fluorescent cholangiography of the cystic duct could be obtained earlier ( À 10 minutes) with the new dye in comparison to ICG.…”
Section: Current Limitationsmentioning
confidence: 97%